THE POETIC TYPE GAZEL IN THE OTTOMAN DIVAN LİTERATURE - Leontik, Marija (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
The Ottoman Divan poetry was scarcely known outside modern Turkey. Divan poetry is rich and mystic poetic tradition and lasted for approximately 600 years. This type of poetry was written in Ottoman Turkish with Arabic alphabet. It contains extensive use of Arabic and Persian words along with Turkish words. Most of the poetic forms are taken from the Arabic and Persian poetic tradition The gazel was the most famous poetic type in the Divan poetry. Many lyric gazels are allegorical and mystical. Gazel generally deals with topics related to lovers, love, nature, God, etc.